EFFICACY OF LEFLUNOMIDE IN PATIENTS PRESENTING WITH RHEUMATOID ARTHRITIS - Sajjad, Faisal; Bilal, Muhammad; Khattak, Saima; Khattak, Muhammad Bilal; Khan , Yaseen; Khan, Ashraf Ali (Khyber Journal of Medical Sciences, 2022)
Objective: To determine the efficacy of leflunomide in patients presenting with rheumatoid arthritis. Methods: This descriptive case series was conducted in the Medicine Department, Lady reading Hospital, Peshawar, for a period of six months on 158 patients. Thorough history, detailed clinical examination and necessary investigations (Full blood count, ESR, Blood glucose, ALT, creatinine & RA Factor) were carried out and DAS28 score was calculated. All diagnosed patients meeting criteria were started on Leflunomide 20 mg daily. During the follow up appointments, DAS28 Score was recalculated; blood counts, creatinine and liver function tests were performed. Effectiveness assessment was done on the basis of DAS28 score. Confounding variables were controlled by strictly following exclusion criteria based on history, clinical examination and investigations. Results: In this study mean age was 43 ± 9.38 years. Seventy eight percent patients were female while 22% patients were male. More over in 65% of the patients leflunomide was effective and in 35% patients it was not effective. Conclusions: Our study concludes that leflunomide was 65% effective in patients presenting with rheumatoid arthritis